Self-Assembled CMC/UiO-66-NH2 Membrane with Anti-Crude Oil Adhesion Property for Highly Efficient Oil-Water Separation - Ma, Lan (Langmuir : the ACS journal of surfaces and colloids, 2022)
Developing the high-anti-fouling membrane has kept continuous attention in oil/water emulsion treatment. However, the majority of works on anti-fouling membranes mainly focused on low-viscosity oils, which greatly limited the development and application of a membrane to face the real crude oil wastewater. Inspired by the hydrophilicity of sodium carboxymethyl cellulose (CMC) and zirconium base metal-organic frame (Zr-MOF), an anti-oil-fouling CMC/UiO-66-NH2 composite membrane was constructed by a self-assembly method. Profiting from the hydrophilicity and micro-nanostructure of the CMC/UiO-66-NH2 layer, the obtained CMC/UiO-66-NH2 membranes displayed underwater superoleophobicity and desired oil resistance. It could display the effective separation capability with 1282 ± 62 to 6160 ± 81 L/(m2·h·bar) and above 99.08% toward the different light oil emulsions. More importantly, the CMC/UiO-66-NH2 membrane displayed ultralow crude oil adhesion behaviors toward the crude oil emulsions, which could achieve a considerably high flux (746 ± 60 to 5224 ± 87 L/(m2·h·bar)). Furthermore, electrostatic interaction and physical enwinding-wrapping between CMC and UiO-66-NH2 also endowed the composite membranes with outstanding stability. After immersing the as-prepared membranes into the harsh environments for 24 h, the membranes still maintained high underwater-oil contact angles (UWOCA > 155°) and separation ability (oil rejection was above 99.0%). Therefore, CMC/UiO-66-NH2 composite membranes could demonstrate promising prospects in real oily emulsion treatment